Aerobic exercise induces tumor suppressor p16INK4a expression of endothelial progenitor cells in human skeletal muscle - Jinfu Wu (2020)
Aerobic exercise induces oxidative stress and DNA damage, nevertheless, lowers cancer incidence. It remains unclear how genetic stability is maintained under this condition. Here, we examined the dynamic change of the tumor suppressor p16INK4a in cells of skeletal muscle among young men following 60-min of aerobic cycling at 70% maximal oxygen consumption (V̇O2max). Rg1 (5 mg, an immunostimulant ginsenoside) and placebo (PLA) were supplemented 1 h before exercise. Data from serial muscle biopsies shows unchanged p16INK4a+ cells after exercise followed by a considerable increase (+21-fold) in vastus lateralis muscle 3 h later. This increase was due to the accumulation of endothelial progenitor cells (p16INK4a+/CD34+) surrounding myofibers and other infiltrated nucleated cells (p16INK4a+/CD34-) in necrotic myofibers. During the Rg1 trial, acute increases of p16INK4a+ cells in the muscle occurred immediately after exercise (+3-fold) and reversed near baseline 3 h later. Rg1 also lowered IL-10 mRNA relative to PLA 3 h after exercise. Post-exercise increases in VEGF mRNA and CD163+ macrophages were similar for PLA and Rg1 trials. Conclusion: The marked increases in p16INK4a protein expression of endothelial progenitor cells in skeletal muscle implicates a protective mechanism for maintaining genetic stability against aerobic exercise. Rg1 accelerates resolution of the exercise-induced stress response.